Age‐specific cost and public funding of a live birth following assisted reproductive treatment in Japan. Issue 5 (2nd April 2014) - Maeda, Eri; Ishihara, Osamu; Saito, Hidekazu; Kuwahara, Akira; Toyokawa, Satoshi; Kobayashi, Yasuki
Abstract Aim The aim of this study was to calculate and assess the cost of assisted reproductive technology (ART) treatment cycles and live‐birth events in Japan in 2010. Material and Methods We performed a retrospective analysis of 238 185 ART cycles, registered with the national registry of assisted reproductive treatment during 2010. Costs were calculated, using a decision analysis model. Results The average cost per live birth was ¥1 974 000. This varied from ¥1 155 000 in women aged < 30 years to ¥50 189 000 in women aged ≥ 45, which was 29.6 times higher than that of women aged 35–39 years. This rose sharply in the early 40s and upwards. Public funding per live birth was ¥442 000. This was ¥6 118 000 in women aged ≥ 45, 15.4 times higher than that of the 35–39‐year‐old age group. Conclusions The costs and public funding of a live birth after ART treatment rises with age due to the lower success rates in older women. It may provide economic background to improve the current subsidy system for ART and to provide practical knowledge about fertility for the general population.